Interaction between obesity and asthma in children and adolescents with hypertension based on NHANES 2007–2020 - Ma, Yizhe; Wang, Luchun; Tao, Mingyan; Bao, Zhidan; Yu, Renqiang; Liu, Guihua; Liu, Jing; Li, Hu (Frontiers in Public Health, 2025)
ObjectivesThis study aims to elucidate the relationship between obesity and asthma in children and adolescents with hypertension based on the 2007–2020 National Health and Nutrition Examination Survey (NHANES).MethodsWeighted logistic regression models assessed obesity and asthma’s effects on hypertension risk, reported as odds ratio (OR) and 95% confidence interval (CI).ResultsA cross-sectional analysis of 10,838 NHANES individuals aged 8–17 found 630 (5.8%) had hypertension, with significant differences in age, sex, poverty-to-income ratio, low birth weight, presence or absence of obesity and asthma, triglyceride concentration, fasting glucose concentration, and tobacco exposure compared to those without hypertension (p < .05). After adjusting for all covariates, children and adolescents with obesity or asthma had a higher risk of hypertension (obesity: adjusted OR 2.14, 95% CI 1.7–2.7; asthma: adjusted OR 1.43, 95% CI 1.1–1.9). Individuals with both obesity and asthma showed a significantly higher risk of hypertension compared to those without these conditions (adjusted OR 2.87, 95% CI 1.9–4.4) (p < .001). The synergistic effect of childhood obesity and asthma on hypertension risk remained robust after the stratified subgroup analysis based on age, sex, birth weight, and tobacco exposure.ConclusionThis study demonstrates that obesity and asthma exert a synergistic effect on childhood hypertension, emphasizing the need for comprehensive interventions targeting weight management and asthma control. There is a pressing need for future research to delve deeper into the mechanisms underlying the interactions between childhood asthma, obesity, and hypertension.